Late Cenozoic vertebrates from the southern Pampean Region: systematic and bio-chronostratigraphic update - Deschamps, Cecilia Marcela (2016)
The knowledge of the vertebrate systematics and bio-chronostratigraphy of late Cenozoic from the southwest of the Buenos Aires Province is updated. The study is focused on 12 localities that encompass the latest Miocene to the Holocene. Biochronologic units were identified and correlated to those of other areas of the Pampean Region. Farola Monte Hermoso, Bajo San José and Playa del Barco outstand because they yielded a large amount of fossil remains. In turn, the quarries near Grünbein allowed refining the age of "Huayquerian" faunas and their relationship with "Montehermosan" ones. The localities Cantera Seminario, Barrancas de Sarmiento, Cantera Vialidad, and Cantera Relleno Sanitario are assigned to the latest Miocene-earliest Pliocene; Farola Monte Hermoso and Las Oscuras, to the Early Pliocene; Bajo San José to the Middle Pleistocene; Puesto La Florida, Chacra Santo Domingo, and García del Río to the Late Pleistocene-Holocene; Playa del Barco to the Late Pleistocene; Pliocene s.l., and Pleistocene-Holocene levels are exposed at Balneario Saldungaray.